70 Asas-Nanp Symposium Roundtable Discussions. (21st September 2022) - Menendez, Hector M
Abstract: The power and utility of modeling approaches are only as good as the animal scientist's ability to apply them. Critical to this ability is knowledge of what tools are available, how they can be applied, and where to find resources to turn ideas into action. After experiencing a hands-on workshop on Agent-Based Modeling in Agriculture and Making Sense of Big Data, Machine Learning, and Modeling, the National Animal Nutrition Program-Pre-Conference Symposia attendees will have a chance to debrief. This roundtable provides a time to ask critical questions and to raise ideas regarding challenges and opportunities regarding modeling training and implementation to benefit animal science research and student training. Finally, updates will be given to provide a further vision of the next steps regarding the National Animal Nutrition Program's efforts in mathematical modeling.